Analisis Kekuatan Asphalt Concrete Wearing Course (AC-WC) dengan Serbuk Ban Bekas Sebagai Zat Aditif - Erna Frida; Ganda Parasian Damanik (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
Research on the effect of the composition of Used Tires powder as additives to the strength of Asphalt Concrete Wearing Course (Ac-Wc). Before the making of the specimen, do Design and mixed (mix design) that includes planning, determination and measurement of asphalt composition of each fraction of each kind of aggregate, asphalt, and the composition of the powder used tires. After the job mix, made with a sample weight of 1200 g, and by varying the composition of the powder used tires 5%, 10%, and 15% of the weight aspal.Pencampuran carried out at a temperature of 150oC. Methods of testing is done by using the Marshall test ie based on the results of Stability, Flow and Marshal Quontent. The results showed that the value of stability and flow SNI 03-1737-1989 still meet the standards for the composition of the powder used tires 5%, 10% and 15% and for the Marshal Quontent has met the standard of SNI 03-1737-1989 on the composition of 10%.